Parity and Risk of Death from Gallbladder Cancer among a Cohort of Premenopausal Parous Women in Taiwan - Chan, Te-Fu (Int J Environ Res Public Health, 2015)
Little epidemiologic research has been done on the etiology of gallbladder cancer (GC). This cohort study was undertaken to examine whether there is an association between parity and risk of death from GC. The study cohort consisted of 1,292,462 women who had a first and singleton childbirth between 1 January 1978 and 31 December 1987. We tracked each woman from the time of their first childbirth to 31 December 2009, and their vital status was ascertained by linking records with the computerized mortality database. Cox proportional hazard regression models were used to estimate the hazard ratios (HR) of death from GC associated with parity. There were 257 GC deaths during 34,980,246 person-years of follow-up. The mortality rate of GC was 0.73 cases per 100,000 person-years. As compared with women who had given birth to only one child, the adjusted HR was 1.20 (95% CI = 0.79–1.83) for women who had two children, 1.47 (95% CI = 0.95–2.29) for women who had three children, and 1.68 (95% CI = 0.99–2.85) for women with four or more births. There was a significant increasing trend in the adjusted HRs for GC with increasing parity. The findings suggested that premenopausal women of higher parity may increase the risk of death from GC.